2020
DOI: 10.34117/bjdv6n2-019
|View full text |Cite
|
Sign up to set email alerts
|

Influência da microalga chlorella vulgaris no desempenho zootécnico do camarão marinho litopenaeus vannamei

Abstract: Influência da microalga chlorella vulgaris no desempenho zootécnico do camarão marinho litopenaeus vannamei Influence of microalgae chlorella vulgaris on zoothenic performance of marine shrimp litopenaeus vannamei

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The zootechnical indices in FF were better, possibly due to the higher lipid concentration of the biomass that influenced the shrimp immunity, higher average weight and final biomass obtaining better productivity and profitability. Silva et al (2020b), added 0.5% dry biomass of C. vulgaris to the feed and compared it with the commercial diet of L. vannamei. Similar to the present study, the authors found greater final biomass and productivity when adding algal biomass, with an increase of 1.05 times compared to the commercial diet.…”
Section: Shrimp Zootechnical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The zootechnical indices in FF were better, possibly due to the higher lipid concentration of the biomass that influenced the shrimp immunity, higher average weight and final biomass obtaining better productivity and profitability. Silva et al (2020b), added 0.5% dry biomass of C. vulgaris to the feed and compared it with the commercial diet of L. vannamei. Similar to the present study, the authors found greater final biomass and productivity when adding algal biomass, with an increase of 1.05 times compared to the commercial diet.…”
Section: Shrimp Zootechnical Parametersmentioning
confidence: 99%
“…The feed must have a high content of proteins, lipids, vitamins and minerals (Gao et al, 2019), important substances for the development of the shrimp and that are part of the composition of C. vulgaris in the necessary amounts. Silva et al (2020b), added 0.5% C. vulgaris dry biomass to the feed and compared it with the commercial diet of L. vannamei. The authors found greater final biomass and productivity when adding algal biomass, with an increase of 1.05 times compared to the commercial diet.…”
Section: Introductionmentioning
confidence: 99%